Diagnostics and Management Challenges of Nonpuerperal Uterine Inversions – Case Series - Sasotya RS; Rinaldi A; Achmad ED; Ma'soem AP; Praharsini K; Imantika E; Wulandari F; Nathania N; Tjandraprawira KD (Dove Medical Press, 2024)
RM Sonny Sasotya, Andi Rinaldi, Eppy Darmadi Achmad, Aria Prasetya Ma'soem, Kania Praharsini, Efriyan Imantika, Fridya Wulandari, Nathania Nathania, Kevin Dominique Tjandraprawira Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Bandung, IndonesiaCorrespondence: Kevin Dominique Tjandraprawira, Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Jalan Pasteur No. 38, Bandung, 40161, Indonesia, Email kevin14007@mail.unpad.ac.idPurpose: Non-puerperal uterine inversion (NPUI) is a rare gynaecological entity with unknown actual incidence. It presents diagnostic and surgical challenges, due to its rarity and lack of clinical experience.Methods: Case series of 5 NPUI cases.Case Description: (1) A 44-year-old P3A0 presented with chronic profuse vaginal bleeding and a prolapsed pedunculated fibroid measuring 9x8x7 cm. In theatre, the pedunculated fibroid was extirpated. Haultain procedure was performed to reposition the uterus, followed by suturing the uterus. (2) A 65-year-old P4A0 presented with a solid vaginal mass, with brisk bleeding measuring 10x10x8 protruding from the introitus. In theatre, the mass was excised, followed by Kustner procedure and a subtotal hysterectomy. (3) A 46-year-old P1A1 presented with a large pedunculated fibroid, hypovolemic shock and loss of consciousness. Upon presentation, she was in shock and severely anaemic (Hb 1.4 gr/dL). In theatre, the fibroid was excised followed by uterine repositioning. A large left ovarian cyst (Ø 10 cm) was identified. A subtotal hysterectomy and left salpingo-oophorectomy were performed. (4) A 34-year-old P3A0 presented with an acute vaginal lump measuring 10x6x5 cm. She had delivered her infant 2 months prior. In theatre, a Huntington procedure was performed to reposition the uterus, followed by a total abdominal hysterectomy. (5) A 60-year-old P3A0 presented with vaginal mass measuring 10× 10× 8 cm and chronic profuse vaginal bleeding. In theatre, uterine inversion was diagnosed. A Haultain procedure was performed, followed by a total abdominal hysterectomy and bilateral salpingo-oophorectomy. All cases had presented with vaginal mass and bleeding to varying degrees. The degree of inversion required various procedures (eg, Kustner, Haultain, Huntington) and different forms of hysterectomy.Conclusion: Non-puerperal uterine inversion is a difficult pathology. Management is always surgical with different types of hysterectomy performed. With conservative surgery, Kustner, Huntington and Haultain procedures are indicated according to the severity and uterine position.Keywords: uterine inversion, hysterectomy, diagnosis